Pengaruh Debt to Equity Ratio, Current Ratio, dan Total Asset Turnover terhadap Return on Assets pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia Periode 2018–2022 - Mardiah, Ainun (Undergraduate Program in Accounting, Department of Accounting, Faculty of Economics and Business, Universitas Tanjungpura, 2024)
This study examines the effects of the debt-to-equity ratio, current ratio, and total asset turnover on return on assets in mining companies listed on the Indonesia Stock Exchange during the 2018–2022 period. The study employs a quantitative approach using secondary data obtained from company financial statements. The sample was selected through purposive sampling and consisted of 10 companies, resulting in 50 firm-year observations. Data were analyzed using descriptive statistics, classical assumption tests, multiple linear regression, and hypothesis testing with SPSS version 25. The results show that the debt-to-equity ratio and current ratio have negative and significant effects on return on assets, while total asset turnover has no significant effect. Simultaneously, the three independent variables significantly affect return on assets. The adjusted coefficient of determination is 12.4%, indicating that the research model explains 12.4% of the variation in return on assets.